2021
DOI: 10.1126/sciadv.abi8065
|View full text |Cite
|
Sign up to set email alerts
|

Continuous rise of the tropopause in the Northern Hemisphere over 1980–2020

Abstract: Continued rise of the tropopause after 2000 in the Northern Hemisphere is mainly due to tropospheric warming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 74 publications
(121 reference statements)
8
36
1
Order By: Relevance
“…According to Meng et al (2021) the highest trend of LRT height is covering latitudinal band 30°N to 40°N and this possibly caused by the tropical widening and subtropical jet poleward shift over the past four decades (Staten et al, 2018), showing high agreement with our findings. In case of ERA5, there is no significant expansion or contraction at both hemispheres.…”
Section: Subjective Criterion For Telsupporting
confidence: 90%
See 1 more Smart Citation
“…According to Meng et al (2021) the highest trend of LRT height is covering latitudinal band 30°N to 40°N and this possibly caused by the tropical widening and subtropical jet poleward shift over the past four decades (Staten et al, 2018), showing high agreement with our findings. In case of ERA5, there is no significant expansion or contraction at both hemispheres.…”
Section: Subjective Criterion For Telsupporting
confidence: 90%
“…In recent years, monitoring the tropopause has received an increased attention for climate change studies. Many studies signified the tropopause rise as a result of the troposphere warming caused by the increase of the GHGs emissions in the atmosphere (Meng et al, 2021;Pisoft et al, 2021). The tropopause characteristics are important for the understanding of the exchange of troposphere-stratosphere (Holton et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…We use standard ordinary‐least‐squares (OLS) regression and fit a linear trend, intercept and the multivariate ENSO index (MEI, Wolter & Timlin, 1993) version 2. Similar principles have been used in analysis of global temperatures (e.g., Foster & Rahmstorf, 2011) and tropopause height (Meng et al., 2021). The linear trend captures WCH tendencies regardless of the cause, and our dWCH/dMEI captures variations that correspond instantaneously to multivariate ENSO index (MEI), again regardless of mechanism.…”
Section: Methodsmentioning
confidence: 98%
“…In addition, regional mean vertical motion was significantly enhanced in the lower troposphere (Figure S2 in Supporting Information ). Previous studies have indicated that both the tropopause and the boundary layer exhibit obvious increases and that the increasing height of the boundary layer is related to the extent of surface warming (Lin et al., 2017; Lorenz & DeWeaver, 2007; Meng et al., 2021). Furthermore, Zhao et al.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, regional mean vertical motion was significantly enhanced in the lower troposphere (Figure S2 in Supporting Information S1). Previous studies have indicated that both the tropopause and the boundary layer exhibit obvious increases and that the increasing height of the boundary layer is related to the extent of surface warming (Lin et al, 2017;Lorenz & DeWeaver, 2007;Meng et al, 2021). Furthermore, Zhao et al (2012) indicated that the increased soil moisture resulted in increased evapotranspiration and surface cooling, followed by asymmetrical surface warming, which altered the regional wind fields and enhanced the ascending motion in the low troposphere.…”
Section: Mechanism Of Increasing Precipitation Produced By Internal M...mentioning
confidence: 98%